NYADHAR TRADITION AND SYMBOLIC INTERACTION OF PANCASILA VALUES IN SUMENEP PINGGIRPAPAS RESIDENTS - Yusro, Lailatul (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2023)
Indonesia is rich in the values of the local wisdom of its people. The Nyadhar tradition as an element of the national cultural heritage passed down from generation to generation by the community is a cultural entity of salt farmers in the suburbs of Sumenep papas which is full of Pancasila symbolic values. The purpose of this study was to find out how the ritualization of the Nyadhar cultural tradition in the Pinggirpapas community in Kebundadap Barat Village and how the symbolic expression of Pancasila values can appear in this cultural interaction. This study uses qualitative methods with a naturalistic approach. To get data from data sources used observation, interviews and documentation techniques. The results showed that: (1) Nyadhar cultural rituals had been going on for a long time, starting from the first discovery of salt by Syeh Anggosuto, who spoke of growing salt. as a livelihood for the community by doing Nyadhar as an expression of gratitude to God who has provided sustenance through salt, and an expression of gratitude to Syeh Anggasuto who has taught and given knowledge in the form of how to make salt, (2) There is an interaction between Nyadhar cultural values and cultural values Pancasila values. Religious values, human values, values of unity and harmony, values of democracy through deliberation activities and the fifth value